Experimental Investigation of the Adsorption and Desorption Kinetics on an Open-Structured Asymmetric Plate Heat Exchanger; Matching Between Small-Scale and Full-Scale Results - Mikhaeil, Makram; Gaderer, Matthias; Dawoud, Belal (Frontiers in Energy Research, 2022)
This paper introduces the results of an experimental study on the adsorption and desorption kinetics of a commercially available, open-structured asymmetric plate heat exchanger adapted to act as an adsorber/desorber for the application in adsorption heat transformation processes. In addition, a volumetric large temperature jump (V-LTJ) kinetic setup was applied to measure the adsorption and desorption kinetics of a small-scale adsorbent sample prepared dedicatedly to be representative for the adsorbent domain inside the investigated adsorber plate heat exchanger (APHE). All kinetic results of the small-scale adsorbent sample and the APHE were fitted into exponential forms with a single characteristic time constant (τ) with a coefficient of determination (R2) better than 0.9531. A very good matching between the small-scale and full-scale adsorption kinetic measurements was obtained, with an average relative deviation of 12.3% in the obtained τ-values. In addition, the kinetic data of the small-scale adsorbent sample were utilized for estimating the expected specific instantaneous and moving average powers of the evaporator/condenser heat exchanger. The average relative deviation (ARD) between the moving average specific evaporator powers obtained from the small-scale and the full-scale measurements amounts between 5.4 and 15.1%.